2017
DOI: 10.5664/jcsm.6654
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome and Sleep-Wake Disturbances in Pregnancy

Abstract: Study Objectives: To estimate the association of restless legs syndrome (RLS) and its frequency with sleep-wake disturbances in pregnancy. Methods: A cohort of 1,563 women in their third trimester of pregnancy were recruited from prenatal clinics between March 2007 and December 2010. Demographic, pregnancy, and delivery data were extracted from medical records and sleep information was collected with questionnaires. To diagnose RLS, we used standardized criteria of RLS symptoms and frequency that were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 46 publications
2
25
2
Order By: Relevance
“…Most recently, Dunietz et al queried a cohort of 1,563 women in the third trimester of pregnancy using standardized RLS questionnaires and found a prevalence of 36%, with moderate-to-severe RLS in half. 72 This is the first large study to investigate and report a higher incidence of self-reported poor sleep quality and more excessive daytime sleepiness in pregnant women with RLS. These symptoms were proportional to RLS severity.…”
Section: Rls and Pregnancy Outcomesmentioning
confidence: 96%
“…Most recently, Dunietz et al queried a cohort of 1,563 women in the third trimester of pregnancy using standardized RLS questionnaires and found a prevalence of 36%, with moderate-to-severe RLS in half. 72 This is the first large study to investigate and report a higher incidence of self-reported poor sleep quality and more excessive daytime sleepiness in pregnant women with RLS. These symptoms were proportional to RLS severity.…”
Section: Rls and Pregnancy Outcomesmentioning
confidence: 96%
“…RLS has been associated with increased odds of sleepwake disturbances such as poor sleep, poor daytime function, and excessive daytime sleepiness in pregnancy. 74 There also seems to be an association between hypertensive disorders of pregnancy and RLS diagnosed by using international RLS criteria in some studies, 75,76 in which women with RLS are more likely to have a hypertensive disorder of pregnancy. Conversely, pregnant women with hypertensive disorders also seem to have a higher risk of meeting RLS criteria, 77 suggesting a potential metabolic process underlying the pathogenesis of RLS in pregnancy and a possible bidirectional relation.…”
Section: Rls/willis-ekbom Diseasementioning
confidence: 99%
“…24 Hence, conditions that result in poor sleep such as RLS, as demonstrated in this study, become critical to identify and possibly important to treat pharmacologically. The research by Dunietz et al 18 and others 14 elevate the diagnosis of RLS in pregnancy from a self-limited condition that would likely resolve postpartum to one with potential adverse obstetric events and beg for studies evaluating the efficacy and outcome of treating RLS in pregnancy.…”
Section: Commentary Shaking Up Perspectives Of Restless Legs Syndromementioning
confidence: 99%
“…Dunietz et al 18 recruited a total of 1,563 women in their third trimester of pregnancy. The study aimed at assessing the prevalence of RLS using standardized criteria for the diagnosis 19 and examining the effect of RLS severity on sleep-wake disturbances using the generalized sleep disturbance scale, 20 as well as associations with delivery outcomes.…”
Section: Commentary Shaking Up Perspectives Of Restless Legs Syndromementioning
confidence: 99%